The resonance between the electromagnetic field and electrons in the helicon plasma source of a magnetoplasma rocket engine - Yang, Zhenyu; Fan, Wei; Han, Xianwei; Tan, Chang (Frontiers in Physics, 2023)
The helicon plasma source is of great significance for the magnetoplasma rocket engine (MPRE) to be used as an effective propulsion device. In this paper, a multi-fluid, two-dimensional, axisymmetric model coupled with the electromagnetic field was developed to simulate the helicon plasma source in the MPRE. The simulation results demonstrate that the operation mode of the helicon plasma source in the MPRE gradually converts to a high-order wave mode and the resonance between the electromagnetic field and electrons is observed; due to the resonance, the deposit power density inside the plasma increases significantly, and the plasma density is two orders of magnitude higher than that in the inductively coupled plasma source. As the magnetic field intensity increases, the helicon plasma source enters into a high-order wave mode, which suggests that the MPRE can improve the utilization rate of the working medium by a stronger magnetic field.